2012
DOI: 10.3928/01477447-20120327-15
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Pancapsular Plication for Multidirectional Shoulder Instability in Overhead Athletes

Abstract: Treating shoulder multidirectional instability with an open stabilization procedure has been reported to have good results. However, few studies exist of arthroscopic plication, especially in overhead athletes. The purpose of this study was to evaluate the clinical outcomes of arthroscopic pancapsular plication for multidirectional instability in overhead athletes.Twenty-three athletes with symptomatic multidirectional instability were treated with arthroscopic pancapsular plication and evaluated at a mean fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Numerous studies done after that have reported favourablemid term or long term outcomes on functional recovery, various scores and shoulder stability [10,64,65] . Post surgical studies on athletes have reported both positive [66,67] as well as unsatisfactory [68] results on successful return to sporting activities at the top or pre-injury levels. The RI closure also leads to an improvement in both the static and the dynamic restraints which enhances the effect on the shoulder stability and function [69] .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies done after that have reported favourablemid term or long term outcomes on functional recovery, various scores and shoulder stability [10,64,65] . Post surgical studies on athletes have reported both positive [66,67] as well as unsatisfactory [68] results on successful return to sporting activities at the top or pre-injury levels. The RI closure also leads to an improvement in both the static and the dynamic restraints which enhances the effect on the shoulder stability and function [69] .…”
Section: Resultsmentioning
confidence: 99%
“…However, the present study does highlight the fact that patients with a traumatic onset of MDI are more likely to return to sports participation than those whose MDI had an atraumatic onset (83% vs 44%, respectively). Looking specifically at overhead athletes, a recent publication by Ma et al 16 evaluated pancapsular plication for MDI in 25 overhead athletes with a mean age of 23 years (range, 19-33 years) in 17 men and 8 women. All patients reported good-to-excellent results based on ASES, Constant, and Rowe scores.…”
Section: Discussionmentioning
confidence: 99%
“…Savoie and Field 20 had patient's wear slings for 1 to 3 weeks, while other protocols recommended sling wear for 6 weeks. 17,21,24 Similarly, there was no consensus with passive or active range of motion. Witney-Lagen et al 22 and Moon et al 23 initiated passive range of motion via pendulums postoperative day 1 or week 1.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…3,4 In the capsular plication procedure, the glenohumeral ligaments are sutured, decreasing the capsule size. 21,22 These procedures have evolved from an open approach to arthroscopic; some surgeons still opt for open procedures. 2,6…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation